Analysis of Remuneration System Implementation and Job Satisfaction on the Performance of Health Officers at RSI Garam Kalianget, Sumenep Regency - Asad Zainudin; Nurwijayanti (Journal for Quality in Public Health, 2022)
Performance is a work achieved by a person in carrying out the tasks assigned to him based on skills, experience, sincerity and time. Performance can be equated with work performance, and thus employee performance is a work achievement achieved by an employee in carrying out their duties and targets.. The purpose of this study is to analyzethe effect of the implementation of the remuneration system and job satisfaction on the performance of health workers at the Garam Kalianget Hospital, Sumenep Regency. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe effect of the implementation of the remuneration system and job satisfaction on the performance of health workers at the Garam Kalianget Hospital, Sumenep Regency. The total population is 134 respondents and a sample of 100 respondents is taken using the Simple Random Sampling technique. In the study, it was found that almost half of the respondents had sufficient remuneration in the category of 46 respondents (46%). Most of the respondents have job satisfaction in the moderate category, 54 respondents (54%). Almost half of the respondents have a good performance category as many as 48 respondents (48%).Based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted so it can be concluded that simultaneously there is the effect of remuneration and job satisfaction on the performance of health workers at the Garam Kalianget Hospital, Sumenep Regency with an effect of 76.9%. It is hoped that health workers will be able to be more oriented to the work itself in providing results, impacts, and benefits for the community and for other employees.